ACTIO PAULIANA IN BANKRUPTCY: EFFORTS TO CANCEL DEBTOR'S LEGAL ACTS - Henry Apan; Henny Saida Flora; Etty Sri Wahyuni; Ari Prabowo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Actio pauliana is a fundamental legal instrument in the Indonesian bankruptcy system to protect creditors' interests from debtor's detrimental legal acts. This research aims to analyze the application of actio pauliana based on Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (UUK-PKPU), focusing on filing requirements, burden of proof, and practical challenges in court proceedings. The research method used is normative juridical with statutory, conceptual, and case study approaches. The results show that actio pauliana as an effort to annul debtor's legal acts has a strategic role in maximizing the bankruptcy estate (boedel pailit) for creditor debt settlement. However, the effectiveness of actio pauliana implementation still faces various obstacles, particularly regarding the heavy burden of proof on curators, differing judicial perceptions in assessing debtor fraud elements, and legal protection for good faith third parties. This research recommends the need for reformulating actio pauliana provisions to provide better legal certainty for all parties involved in bankruptcy proceedings.